The magnificence and importance of Caesarea in Acts and archeology - Rios, Cesar Motta (Vox Scripturae - Revista Teológica Internacional, 2016)
In this essay, I propose an introduction to Caesarea Maritima through the reading of key passages of the book of Acts and the consideration of recent archaeological studies. I aim to foment a better visualization of the concrete scenery and cultural context in which certain biblical passages take place. Moreover, throughout this exposition, the reading of pertinent passages in the book of Acts illustrates the relevance of events that have the city as its stage. As a result, it will be evident the relevance of Caesarea for incipient Christianity, as well the importance of the archaeology for its study.
Keywords: Caesarea Maritima; Archaeology; Acts; Herod